Impact of Macroprudential Policy on Demand KPR-FLPP - Retno Febriyastuti Widyawati; Sisti Ujianti; Ermatry Hariani; Andi Lopa Ginting (Economics Development Department, Universitas Negeri Semarang, Indonesia, 2022)
The need for housing is increasing every year, along with the increase in population. However, the increase in housing reached 11.4 million units is not matched by the availability of housing because there are as many as 1.8 million marriages every year, and they need housing. This results in housing prices getting more expensive every year. Therefore, the government, through macroprudential policies, loosened down payments for house purchases so that there was an increase in housing demand. The purpose is to find out whether the macroprudential policy implemented by BI has an impact on the demand for the KPR-FLPP government program by examining the influence factors of inflation, GRDP, interest rates, and LTV on demand KPR-FLPP (financing housing subsidies to income society low from the government issued by a conventional bank and sharia bank) in East Java Province. This study employed Ordinary Least Squares (OLS) model multiple linear regression and time series from Q1:2010 to Q4:2020 for East Java. The macroeconomic variables applied in this study composed dependent variable is the demand for KPR-FLPP. While the independent variables are inflation, GRDP, interest rates, and LTV, with a dummy variable of 0 before LTV and 1 after the LTV. The study concluded that inflation and GRDP have an important role in the demand for KPR-FLPP. It means that inflation and GRDP raised significantly, causing more demand for KPR-FLPP in East Java. This study is expected to give contribution to East Java Government to policy makers to increase demand for KPR-FLPP in East Java.